Towards a Poetics of Conspiracy. (1st December 2021) - Jackson, Rob
This essay reads Rita Wong and Fred Wah's beholden and Christine Stewart's Treaty 6 Deixes to elaborate a concept of conspiratorial poetics in the settler colonial context of Canada. The article figures conspiracy both as the practice of co-respiration and an admission to join in treasonous activities, suggesting that the poetic interventions of Wong, Wah, and Stewart offer models that readers may take up to breathe life into decolonial relationships while conspiring against the normative functions of settler governance.